Jurnalisme dalam Tatanan Neoliberal dan Krisis Demokrasi - Rianto, Puji (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2005)
Applied in most countries, neo-liberalism has shifted the orientation of mass media from the public to the market. Journalism, as a result, tends to be driven by the market in which this leads to the failure of mass media in advancing democracy. This article demonstrates how the market-driven journalism creates the crisis of democracy.